Understanding the Operations of Freight Forwarders : Evidence from Serbia - Mendoza Alcantara, Alejandra; Fernandes, Ana M.; Hillberry, Russell (World Bank, Washington, DC, 2015)
Freight forwarders play a key role in moving goods across international borders. They arrange transport, oversee customs clearance on behalf of their clients, and more generally troubleshoot issues that arise while goods are in transit. This paper reports the results from a survey of 153 freight forwarding firms in Serbia. Respondents report on firm characteristics, operational choices, and conditions at the border posts and terminals where imported goods are cleared for release. One key purpose of the study is to investigate operational trade-offs between time and cost that arise when import shipments are in transit. In three of four hypotheticals, respondents suggest that money savings dominate time savings. Responses regarding real operational decisions such as route choices reinforce this finding. Respondents also reported penalty rates for late delivery of import shipments as well as the value of a typical import shipment. From these responses, it is estimated that the contracted value of one additional (unexpected) day of delivery time in Serbia appears to be approximately 1 percent of the value of the underlying shipment.